The fast diet : lose weight, stay healthy, and live longer with the simple secret of intermittent fasting - Mosley, Michael, 1957-; Spencer, Mimi, 1967- (New York : Atria Books, 2013)
"Is it possible to eat anything you want, five days a week, and become slimmer and healthier as a result? Simple answer: yes. You just limit your calorie intake for two nonconsecutive days each week to 500 calories for women, 600 for men. You'll lose weight quickly and effortlessly, and the joy of the FastDiet is that the side effects are all welcome. The science is easy. Intermittent fasting takes your body out of go-go mode and puts it into survival mode, causing the body to slow production of new cells and repair old ones instead. As a result, you not only lose weight but also reduce your risk of a range of diseases from diabetes and arthritis to cardiovascular disease and even cancer. On top of that, you slow the aging process and boost your brain power. This book brings together the results of new, groundbreaking research to create a dietary program that can be incorporated into your busy daily life, featuring: Forty 500- and 600-calorie meals that are quick and easy to make 8 pages of photos that show you what a typical "fasting meal" looks like the cutting-edge science behind the program. A calorie counter that makes dieting easy, and much more. Far from being just another fad, the FastDiet is a radical new way of thinking about food, a lifestyle choice that doctors are actually recommending for general health. This is your indispensable guide to effective weight loss without sacrificing the foods you love and a scientifically proven way to have your cake and eat it, too"--
"This new diet allows users to eat whatever they like five days a week and then fast (consuming 500-600 calories/day) for two nonconsecutive days--and lose weight quickly and easily"--
Includes bibliographical references and index.
Keywords: Reducing diets -- Recipes; Diet; HEALTH & FITNESS / Diets; HEALTH & FITNESS / General; HEALTH & FITNESS / Weight Loss; Cookbooks